Bem estar em cativeiro: análise e planejamento da ocupação do tempo em macacos-prego (Cebus apella) - LESSA, Miguel Angelo Monteiro (Universidade Federal do Pará, 2014)
Foraging is one of the most important activities and consuming great part of the day time of neotropical primates in the natural environment. In the wild, Capuchins spend up to 80% of their time traveling and foraging in the search for food. On the other side, in captivity no effort is usually required to obtain food. Therefore the opportunity to express foraging activities becomes virtually excluded in captivity. The main objective of this work was to create and evaluate the effectiveness of an environmental enrichment tool called “bowlboard”, designed to difficult access, extending the time devoted to reach food. The observation was carried through in four different contexts, being one in the morning and three in the afternoon, using a focal animal sampling method. The relative duration of each behavioral event was compared in the absence and presence of the enrichment. It was found that the bowller extended foraging time, functioning as instrument of environmental enrichment. A considerable lowering in frequency of abnormal behaviors, while search and manipulation of food was more time consuming.